2022
DOI: 10.1002/adfm.202209201
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive Nitrogen‐Doped sp2/sp3 Hybrid Carbon as a Conductor‐Free Charge Storage Host

Abstract: It is commonly accepted that the increased degree of graphitization leads to a higher electrical conductivity of carbon materials. However, more and more evidence reveals that heteroatom doping on carbon host can also improve the conductivity, owing to the dopant atoms contributing to higher charge delocalization and density of donor states near Fermi level. The reality is, such conductivity improvement from doping is often overwhelmed by graphitized carbon. Although heteroatom‐doped carbon is widely used as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Among them, mesoporous carbon structures with a broad or narrow distribution of pores have recently attracted enormous attention in different fields because of high specific surface area, good chemical and mechanical properties, high thermal stability, large pore volume, and uniform and controllable porous structure. These outstanding properties enable mesoporous structures to be excellent candidates for various practical applications, including as a catalyst and its support, adsorption and separation, energy conversion and storage, environmental remediation, drug delivery, and biomedical applications [12][13][14][15][16][17][18][19]. At first, mesopores in carbon structures were produced by enlarging micropores via oxidation during activation process, such as activated carbons, or at the interstices between carbon particles, such as carbon aerogels.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, mesoporous carbon structures with a broad or narrow distribution of pores have recently attracted enormous attention in different fields because of high specific surface area, good chemical and mechanical properties, high thermal stability, large pore volume, and uniform and controllable porous structure. These outstanding properties enable mesoporous structures to be excellent candidates for various practical applications, including as a catalyst and its support, adsorption and separation, energy conversion and storage, environmental remediation, drug delivery, and biomedical applications [12][13][14][15][16][17][18][19]. At first, mesopores in carbon structures were produced by enlarging micropores via oxidation during activation process, such as activated carbons, or at the interstices between carbon particles, such as carbon aerogels.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the stretching band of C = N moved from 1590 cm −1 to 1602 cm −1 , indicating that melem was almost converted to Azo-CHF completely. In the solid-state 13 C NMR spectra of Azo-CHF (Figure 1d), the signal of N 2 C-N = N-and CN 3 carbons appeared 164 and 156 ppm, respectively, while the signal of CN 3 carbon in melem appeared 154 ppm with a relatively weaker intensity, supporting the shielding of carbons because the overlapping of azo nitrogens and aromatic 𝜋 system of HEP rings in the extended 𝜋-conjugation structure. In the solid-state 15 N NMR spectra of Azo-CHF, the new signal at −268 ppm (-N = N-) emerged (Figure S7, Supporting Information), which further powerfully illustrated the formation of azo bridges from melem.…”
Section: Resultsmentioning
confidence: 80%
“…[6][7][8][9][10][11] Among diverse developed materials, nitrogen-doped carbon with potential electrochemical capability offers considerable perspective for developing high-performance electrode materials. [12][13][14] Graphitic carbon nitride (g-C 3 N 4 ), a layer structure where heptazine (HEP) acts as the primary active cores, is of attractive interest owing to its rich pyridine N active DOI: 10.1002/adfm.202308706 sites as they can not only improve the electro-acitve surface area and wettability of electrode but also endow electrode with pseudocapacitance. [15][16][17] Unfortunately, the electronchemical performance of g-C 3 N 4 is extremely restricted by its poor conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The density functional theory calculations also confirmed improved electronic conductivity and Li storage ability by N-doping. Overall, numerous studies have so far demonstrated the positive effects of N-doping on carbon materials for high-performance electrochemical energy storage devices, such as supercapacitors 29 and rechargeable batteries. 30 However, most studies have only reported the effect of N-dopants on ion adsorption capacity in an uncharged state, little has been devoted to exploring the charge distribution mechanism of NPC under different charged states, as well as the development of costeffective synthetic methods for precise control of N species.…”
Section: Introductionmentioning
confidence: 99%